How things work : the physics everyday life - Bloomfield, Louis (New York : John Wiley & Sons, 1997)
This book is about: The laws of motion; simple mechanical objects; Fluids; Fluids and motion; Mechanical objects and fluids; ...
Keywords: Physics; Physics